A Systematic Review of the Effects of Aromatherpy with Lavender Essential Oil on Depression - Azar Jafari-Koulaee; Forouzan Elyasi; Zohreh Taraghi; Ehteram Sadat Ilali; Mahmood Moosazadeh (University Library System, University of Pittsburgh, 2020)
Introduction: Depression is considered as one of the most serious health issues worldwide, and the search for the most effective and safe treatments for depression is essential. Aromatherapy with lavender have attracted the attention of many researchers due to their low cost and ease of use, so this study was conducted to review of the effects of aromatherapy with lavender essential oil on depression. Methods: This systematic review study was conducted by searching the databases (SID, Magiran, Google-Scholar, Medline via PubMed, Scopus, and Web of Science) by using the keywords such as depression, Lavandula, Lavender, and Aromatherapy, as well as applying OR and AND operators to the end of January 1, 2020 A.D. The inclusion criteria were: 1) Interventional studies that determined keywords were in the title or keywords of the article, 2) aromatherapy was conducted through inhalation or massage, 3) the full text of paper was accessible, and 4) published in English or Persian. Finally, the information obtained from articles was extracted using a checklist. Results: Out of 278 studies, 9 studies were included to the systematic review process after screening and eliminating duplicate papers according to the purpose of the study. Aromatherapy with lavender essential oil was conducted on the patients suffering from migraine, patients with the acute coronary syndrome, patients undergoing hemodialysis, community-dwelling older adult, and postpartum depression. The results obtained from some studies showed the positive effect of aromatherapy with lavender essential oil on depression whereas some studies did not report the effect of aromatherapy with lavender on depression significantly. Conclusion: It seems that aromatherapy with lavender probably can be used as a complementary, simple, and inexpensive method to improve mild and moderate depression. It is recommended to earmark using a collaborative approach and make use of interdisciplinary and psychology specialists as well as complementary medicine in applying aromatherapy with lavender essential oil.